Deep Spectral Feature Aggregation for Hyperspectral–LiDAR Data Fusion in Land Use Classification - Stanley Holm; Terry Phillips; Kartik M. Jha (Computational Intelligence Systems, 2026)
Land use classification is a critical task in remote sensing that requires the integration of complementary data modalities to achieve high accuracy and robustness. Hyperspectral imaging provides rich spectral information across hundreds of narrow bands, while Light Detection and Ranging (LiDAR) offers precise three-dimensional structural data. The fusion of these two modalities presents significant opportunities for improved land cover discrimination, yet it also introduces substantial challenges related to feature alignment, dimensionality, and computational efficiency. This paper introduces a novel framework for deep spectral feature aggregation designed to fuse hyperspectral and LiDAR data in an end-to-end learning architecture. The proposed system employs a multi-stream convolutional neural network that extracts hierarchical spectral and spatial features separately before merging them through an attention-guided aggregation module. Emphasis is placed on system-level considerations including architectural trade-offs, training stability, and deployment scalability. The framework is evaluated on benchmark datasets, demonstrating superior classification accuracy compared to traditional fusion methods. Beyond technical performance, this paper discusses broader implications for infrastructure governance, data equity, and sustainability in large-scale land use monitoring systems. Findings suggest that careful design of feature aggregation pathways can significantly reduce computational overhead while maintaining high accuracy, and that attention mechanisms provide interpretability benefits crucial for policy enforcement. The study also highlights the need for standardized evaluation protocols and open data policies to ensure reproducibility and fairness across diverse geographic regions. This work contributes both a practical fusion architecture and a critical examination of the socio-technical dimensions of integrating advanced remote sensing technologies into operational land use classification pipelines.